Agent oriented software engineering with web applications. (14th February 2005) - Gomez-Sanz, Jorge J.; Fuentes, Ruben
This paper proposes an agent oriented approach to design web applications. Contrary to other research work, this paper considers agents only at the conceptual level because they are convenient abstractions. In the implementation, agents are substituted by more adequate computational entities like Enterprise Java Beans or servlets. The translation from the conceptual level to the implementation is based on the relevance of interactions in both web-applications and Multi-Agent Systems. Throughout the paper, we show the current situation in Multi-Agent systems and what elements are required in a Multi-Agent System implementation.